Assessing bilateral ankle proprioceptive acuity in stroke survivors: An exploratory study - Pan, Li; Xu, Dongyan; Wang, Weining; Rong, Jifeng; Xu, Jinyao; Ferland, Amanda; Adams, Roger; Han, Jia; Zhu, Yulian (Frontiers in Neurology, 2022)
Background Bilateral proprioception deficits were reported in stroke survivors. However, whether bilateral proprioception deficits exist in the ankle joint after stroke was unclear. Ankle proprioception is a significant predictor of balance dysfunction after stroke, and previous studies to date are lacking appropriate evaluation methods. Objectives We want to determine whether the active movement extent discrimination apparatus (AMEDA) is a reliable tool for assessing ankle proprioceptive acuity in stroke survivors and the presence of deficits in ankle proprioception on the affected and unaffected sides in patients after stroke. Methods Bilateral ankle proprioception was assessed in 20 stroke patients and 20 age-matched healthy controls using AMEDA. Test-retest reliability was assessed using the intraclass correlation coefficient (ICC). Results The ICC in the affected and unaffected sides was 0.713 and 0.74, respectively. Analysis of variance revealed significant deficits in ankle proprioception in subacute stroke survivors vs. healthy controls (F = 2.719, p = 0.045). However, there were no significant differences in proprioception acuity scores between the affected and unaffected sides in patients after stroke (F = 1.14, p = 0.331). Conclusions Stroke survivors had bilateral deficits in ankle proprioceptive acuity during active movements compared with age-matched healthy controls, underscoring the need to evaluate these deficits on both sides of the body and develop effective sensorimotor rehabilitation methods for this patient population. The AMEDA can reliably determine bilateral ankle proprioceptive acuity in stroke survivors.